Epistatic interactions between Fc (GM) and FcγR genes and the host control of human immunodeficiency virus replication - Deepe, Raymond N.; Kistner-Griffin, Emily; Martin, Jeffrey N.; Deeks, Steven G.; Pandey, Janardan P. (Human immunology, 2012)
Host genetic factors are thought to contribute to the interindividual differences in the control of human immunodeficiency virus (HIV) replication. The aim of the present investigation was to determine whether genes encoding GM and KM allotypes—genetic markers of immunoglobulin γ and κ chains, respectively—and those encoding Fcγ receptor (FcγR) IIa and IIIa are associated with the host control of HIV replication. A case–control design was employed among HIV-infected subjects, with a group that spontaneously controlled HIV replication (“controllers”) as cases (n = 73) and those who did not control replication as controls (n = 100). Genotyping was performed by polymerase chain reaction–restriction fragment length polymorphism, direct DNA sequencing, and TaqMan genotyping assays. In Caucasian Americans, certain combinations of FcγR and GM genotypes were differentially distributed between controllers and noncontrollers. Among the noncarriers of the FcγRIIa arginine allele, GM21 noncarriers had over 7-fold greater odds of being controllers than the carriers of this allele (odds ratio [OR] = 7.47). These GM determinants also interacted with FcγRIIIa alleles. Among the carriers of the FcγRIIIa valine allele, GM21 noncarriers had over 3-fold greater odds of being controllers than the carriers of this allele (OR = 3.26). These results demonstrate epistatic interactions of genes on chromosomes 14 (GM) and 1 (FcγR) in influencing the control of HIV replication.